A case of LGL leukemia with paucity of erythropoiesis. Issue 12 (29th July 2020) - Razavi, Habib M.
Abstract: The differential diagnosis for neutropenia is large and includes, drug effect, viral infections, sepsis, immune, hypersplenism, and bone marrow disorder. The presence of an autoimmune disorder and large granular lymphocytosis should prompt assessment for immunophenotyping and in select cases a bone marrow biopsy to rule out LGL‐leukemia. Abstract : The differential diagnosis for neutropenia is large and includes, drug effect, viral infections, sepsis, immune, hypersplenism, and bone marrow disorder. The presence of an autoimmune disorder and large granular lymphocytosis should prompt assessment for immunophenotyping and in select cases a bone marrow biopsy to rule out LGL‐leukemia.